The determinants of transnational entrepreneurship and transnational ties' dynamics among immigrant entrepreneurs in ICT sector in Italy. (5th April 2017) - Brzozowski, Jan; Cucculelli, Marco; Surdej, Aleksander
Abstract: This article contributes to the rapidly growing literature on transnational immigrant entrepreneurship by analyzing the determinants of transnational entrepreneurial engagement among immigrants in the ICT sector in Italy. We investigate which factors influence the rise or decline of transnational entrepreneurial involvement with a home country. Our results indicate that longer residence in Italy is associated with smaller propensity to become a transnational entrepreneur. Moreover, we find that the type of transnational ties and the network size have a substantial impact on the dynamics of transnational entrepreneurial engagement.